Alcohol, pregnancy and breastfeeding; a comparison of the 1995 and 2001 National Health Survey data - Giglia, Roslyn; Binns, Colin (Australian Breastfeeding Association, 2008)
Alcohol enters breastmilk by passive diffusion and levels are reflected in maternal blood within 30 to 60 minutes of ingestion. If not timed appropriately, drinking alcohol throughout the period of lactationcan negatively impact on lactation performance and the mental development of the infant. The aim ofthis study was to explore the drinking patterns of pregnant, lactating and other Australian women of child bearing age using the 1995 and 2001 National Health Survey Confidentialised Unit Record Files.Alcohol consumption was categorised according to Guideline 11 from the National Health and Medical Research Council (NHMRC) current Australian Alcohol Guidelines, which state that if pregnant or lactating women choose to drink, over a week, they should have fewer than 7 standard drinks. Despite alow intake by most pregnant and lactating women from both surveys, approximately 16.4% and 1.3% (95% Confidence Interval (CI) 7.0-23.2) of pregnant women from the 1995 and 2001 NHS respectively, and 13% and 16.8% (95% CI -6.5-1.1) of lactating mothers from the 1995 NHS and 2001 NHS respectively, were drinking above this national guideline. There were significantly more pregnant women in the 1995 NHS, and lactating women in the 2001 NHS, exceeding this recommendation. Pregnancy and lactation arevulnerable times of infant growth and development. There is a definite need in Australia for improvedantenatal, and maternal and child health programs that address this significant public health issue.